Strategi Pemasaran Untuk Meningkatkan Penjualan Pupuk Organik Pumakkal - Apriyanto, Andri; Rahayu, Sri Retnaning (Universitas Muhammadiyah Metro, 2023)
Organic fertilizers are fertilizers that come from various materials for making natural fertilizers such as animal manure, animal body parts, plants, which are rich in minerals and are good for the use of soil enrichment. Pumakal fertilizer is one of the organic fertilizers developed by PT Pumahitari to increase production in the agricultural sector and prevent land degradation. Sources of organic fertilizer materials are very diverse, such as Pumakkal organic fertilizer which is made using pineapple waste. It aims to recycle pineapple waste so as to help reduce environmental pollution from the waste. This study aims to determine the marketing strategy to increase sales of Pumakkal organic fertilizer. The method used in this research is descriptive with a qualitative approach. The implementation of marketing strategy plays a very important role in increasing sales of Pumakkal Organic Fertilizer. In implementing the marketing strategy of Pumakkal Organic Fertilizer, currently, three components in the theory of marketing strategy have been implemented, namely segmentation, targeting, and positioning. However, the implementation of Pumakkal's Organic Fertilizer marketing strategy has not been optimal in the targeting and positioning components, so it has not been able to increase sales. The results of the research using the SWOT Matrix of PT. Pumahitari is able to take advantage of existing opportunities with its strengths, this is good for the company to reduce weaknesses and minimize threats in order to increase sales. besides that, it can also be concluded that several developments through consideration of internal factors and external factors of the company can be beneficial for the progress of PT. Pumahitari.